Introduction - O Nuallain, Sean (Cosmos and History: The Journal of Natural and Social Philosophy, 2014)
This is the introduction to the special edition on Foundations of Mind: Cognition and Consciousness and the introduction to the conference at UC University at Berkeley on which the edition is based.